Qualidade da educação a distância e o uso das tecnologias de informação e comunicação - Joshiley Coelho Guindo de Aquino (EaD & Tecnologias Digitais na Educação, 2016)
This article resulted from a study conducted in the course of Postgraduate Sensu Lato Media in Education from the Federal University of Mato Grosso do Sul in 2012. He was elected as an object of study: teacher formation in educational technology through the National Formation Program Continuing Educational Technology (Integrated PROINFO) in the city of Corumbá, State of Mato Grosso do Sul (MS), from 2008 to 2011, but for the purposes of this communication upgraded from the present data. It was defined as problematic the question: how the theoretical and didactic and technological knowledge present in the core courses of the Integrated PROINFO were appropriated and incorporated by the teachers of public schools of basic education of Corumbá- MS? In an attempt to answer that question, it was defined as a general objective: to analyze the process of theoretical and technological appropriation for basic education teachers in achieving the basic courses of the Integrated PROINFO in Corumbá-MS. The research was documentary and theoretical. Search procedures consisted of analytical reading of primary sources that had as empirical basis the edited documents and legislation about the studied object. Secondary sources were based specifically on the analysis of the annual reports prepared by the Educational Technology Center (NTE) and the theoretical dialogue with the authors who study the subject teacher education and information and communication technologies. It was concluded that teachers to use ICT in teaching and methodological activities need to be have the technological fluency and appropriate pedagogical concepts, teaching methods and techniques with ICT.